Polymerase chain reaction analysis as a rapid screening test for diagnosis of fragile X syndrome - Phan CL,; Zubaidah Z,; Gregory A.R.A,; Kamariah MN,; Ten SK,; Maimonah R,; Thilagavathi S, (Penerbit UKM, 2006)
Fragile X syndrome is a result of an unstable expansion of (CGG)n trinucleotide sequences in the FMR-1 (Fragile X Mental Retardation 1) gene site at Xq27. In a normal person, n ranges from 6 to 40 repeats with an average of 30 repeats, whereas in a mutated FMR1 gene the sequence is repeated several times over (stuttering gene). Full mutation occurs when n equals 200 repeats or more. Where n equals 50 to 200 repeats, it is a premutation. Fragile X occurs when the FMR-1 gene is unable to make normal amounts of usable Fragile X Mental Retardation Protein, or FMRP. The amount of FMRP in the body is one factor that determines the severity of the Fragile X syndrome. A person with nearly normal levels of FMRP usually has mild or no symptoms, while a person with very little or no normal FMRP has more severe symptoms. The mechanism for the role of the FMRP gene is still being researched upon. However, it has been observed that large numbers of repeats (more than 200) inactivates the gene through a process of methylation and when the gene is inactivated, the cell may make little or none of the needed FMRP. Inheritance is X-linked with reduced penetrance and the frequency of occurrence goes up through generations. The phenotypic manifestations of fragile-X syndrome vary and are largely dependent on the size of the mutation or premutation. The identification of the fragile site on G banded metaphases is a time consuming and delicate process requiring experience and skill, however, molecular diagnosis using DNA analysis and Southern blotting, even though expensive, is more specific in determining the presence or absence of the gene. This study was aimed to establish a rapid polymerase chain reaction (PCR) based - touch down PCR, as a screening method for fragile X syndrome. A total of six cases were analysed. Of these, one was a known case of Fragile X (T1) diagnosed by conventional cytogenetics, two were from the latter’s family members namely, his mother (T2) and father (T3), and the other two (T4 and T5) were randomly selected from patients presenting with dysmorphic features and delayed development respectively. One normal control (TC) was included. Cytogenetic analyses for detection of the fragile site was carried out in all cases. Two culture systems were used, namely the synchronised lymphocyte culture and the folate - thymidine deficient culture. Stained metaphases from the fragile X cultures were screened for the presence of the fragile site on the X chromosome. G-banded karyotyping was done using an image analyser to exclude presence of chromosomal abnormalities. DNA was extracted from these samples and amplified by touch-down PCR. Cytogenetic analysis revealed a folate-sensitive fragile site in the affected male, but none in the other five samples. G-banded karyotyping exhibited no additional chromosomal abnormalities. All extracted DNA samples were successfully amplified. Five of the samples showed presence of the product at the expected band at 552bp, excluding the presence of an expansion of CGG segment of the FMR-1 gene. The absence of a band in an affected individual, suggested a fully mutated allele of FRAXA (Folate Sensitive Fragile Site at Xq28). We succeeded in establishing a slightly modified touch-down PCR analysis. Our study indicates that PCR testing offers a rapid and specific method for screening of normal allele and full mutation of the fragile X gene. We suggest this technique to be applied as a complementary tool for cytogenetic analysis to detect the FRAXA gene